The Determinants of Rising Informality In Brazil : Evidence From Gross Worker Flows - Bosch, Mariano (The World Bank, 2007)
This paper studies gross worker flows to explain the rising informality in Brazilian metropolitan labor markets from 1983 to 2002. This period covers two economic cycles, several stabilization plans, a far-reaching trade liberalization, and changes in labor legislation through the Constitutional reform of 1988. First, focusing on cyclical patterns, the authors confirm that for Brazil, the patterns of worker transitions between formality and informality correspond primarily to the job-to-job dynamics observed in the United States, and not to the traditional idea of the informal queuing for jobs in a segmented market. However, the analysis also confirms distinct cyclical patterns of job finding and separation rates that lead to the informal sector absorbing more labor during downturns. Second, focusing on secular movements in gross flows and the volatility of flows, the paper finds the rise in informality to be driven primarily by a reduction in job finding rates in the formal sector. A small fraction of this is driven by trade liberalization, and the remainder seems driven by rising labor costs and reduced flexibility arising from Constitutional reform